Improving Students' Pronunciation of the Mutamathilah Letters Through TikTok - Saipolbarin Ramli; Badariah Ruslan; Mohd Azrilhisyam Rosden; Siti Rahmah Borham (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Mastering the pronunciation of Arabic mutamathilah letters remains challenging for primary school learners because these letters share similar points of articulation and phonetic characteristics, which often lead to pronunciation errors. To address this challenge, Jawlah TikTok, a gamified, technology-based educational application, was developed as an alternative teaching aid to support pronunciation instruction in Arabic. This study evaluated the application's usability and explored experts' perceptions of its potential to facilitate the teaching of mutamathilah letter pronunciation. The application was developed following the ADDIE instructional design model, with the present study focusing on the Evaluation phase. Usability was assessed by seven Arabic language education experts, selected through purposive sampling, using the USE (Usefulness, Satisfaction, and Ease of Use) Questionnaire. The collected data were analyzed using the Percentage Calculation Method (PCM). The findings revealed an overall usability score of 92.42%, comprising usefulness (93.14%), ease of use (90.85%), ease of learning (92.85%), and satisfaction (92.85%), indicating a high level of expert agreement regarding the application's pedagogical usability. The experts also agreed that the gamified features of Jawlah TikTok have the potential to enhance students' motivation, engagement, and classroom interaction in Arabic language learning. These findings provide empirical evidence that Jawlah TikTok is a pedagogically sound and highly usable gamified application for supporting Arabic pronunciation instruction in primary education, while offering practical guidance for integrating digital technologies into Arabic language classrooms.